Generalized idiopathic root resorption: a case report - NEHA BHATT & ISABELLE HOLROYD (IAPD and Blackwell, 2008)
Root resorption is broadly classified by site of origin as internal or external. Both external and internal root resorption can be caused by trauma, orthodontic tooth movement, and may be a result of idiopathic resorption.